FXR expression is associated with dysregulated glucose and lipid levels in the offspring kidney induced by maternal obesity - Glastras, Sarah J. (Nutr Metab (Lond), 2015)
BACKGROUND: Maternal obesity is associated with dysregulation of glucose and lipid metabolism with consequent exposure of the fetus to an abnormal metabolic milieu. It is recognized that maternal obesity predisposes offspring to chronic kidney disease (CKD). We aimed to determine whether the nuclear Farnesoid X receptor (FXR), known to play a role in maintaining homeostasis of glucose and lipid metabolism, is involved in renal injury in offspring of obese mothers. METHODS: Maternal obesity was established in a rat model by feeding dams with high-fat diet prior to and during pregnancy and lactation. The offspring’s kidneys were examined at postnatal Day 1and Day 20. Human kidney 2 (HK2) cells were exposed to high glucose with or without the FXR agonist GW4064 or when FXR mRNA was silenced. RESULTS: Glucose intolerance in the offspring of obese mothers was evident at weaning, with associated downregulation of renal FXR expression and upregulation of monocyte chemoattractant protein-1 (MCP-1) and transforming growth factor-β1 (TGF-β1). HK2 cells exposed to high glucose had reduced FXR expression and increased MCP-1, TGF-β1, fibronectin and collagen IV expression, which was reversed in the presence of GW4064. FXR-silenced HK2 cells had amplified pro-inflammatory and pro-fibrotic markers under high glucose conditions. CONCLUSIONS: Maternal obesity influences renal expression of pro-inflammatory and fibrotic factors that predispose the offspring to CKD. This was associated with the downregulation of the renal FXR expression suggesting a potential protective role for FXR. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12986-015-0032-3) contains supplementary material, which is available to authorized users.